Retaining Participants in Outpatient and Community-Based Health Studies: Researchers and Participants in Their Own Words - Odierna, Donna H. (Sage Open, 2014)
Loss to follow-up can introduce bias into research, making it difficult to develop inclusive evidence-based health policies and practice guidelines. We aimed to deepen understanding of reasons why participants leave or remain in longitudinal health studies. We interviewed 59 researchers and current and former research participants in six focus groups (n = 55) or interviews (n = 4) at three study centers in a large academic research institution. We used minimally structured interview guides and inductive thematic analysis to explore participant-level, study-level, and contextual participation barriers and facilitators. Four main themes emerged: transportation, incentives and motivation, caregiver concerns, and the social and physical environment. Themes shared crosscutting issues involving funding, flexibility, and relationships between researchers and research participants. Study-level and contextual factors appear to interact with participant characteristics, particularly socioeconomic status and disease severity to affect participant retention. Participants’ characteristics do not seem to be the main cause of study dropout. Researchers and funders might be able to address contextual and study factors in ways that reduce barriers to participation.